The transition to democracy in Bolivia - Malloy, James M. (1985)
​The central subject of this article is the analysis of historical developments relating to the establishment of formal democracy in Bolivia as well as the examination of the structural inefficiency and weakness of those institutions which should support the democraiic process. In the authors' opinion, the lack of viability of democracy in Bolivia is largely due to the fact that political parties play no effective role in acting as mediators between the State and Society, thereby making impossible the process of aggregation of divergent demands and thus the stable support from society to the State. On the contrary, to the extent that "caudillista" tendencies prevail among the principal Bolivian leaders, day-to-day politics will encourage the practice of clientelist relations which will erode the very viability of formal political institutions. Thus the authors underline the fact that, faced with tumultuous and complex alliances between civílians and the military, the patterns of behavior of the State will suffer from a perverse dimensión, the evidence of which is to be found in the demands tnade by the particular government in power and its entourage. Their conclusión is that, for the time being, formal democracy in Bolivia is more of an aspiratíon than a reality.​